Environmental consideration in bank’s lending decision: a case study of Bangladesh - Haque, Samina (© 2014 World Review of Business Research, 2016)
This article was published in World Review of Business Research [© 2014 World Review of Business Research] and the definite version is available at :http://www.wrbrpapers.com/static/documents/March/2014/11.%20Samina.pdf The article website is at: http://www.wrbrpapers.com/previous_issue/March/2014